2005
DOI: 10.1144/0061023
|View full text |Cite
|
Sign up to set email alerts
|

The crustal structure and regional development of the Irish Atlantic margin region

Abstract: Duringthe past decade, asuiteofwide-angleseismic reflection/refraction profileshasbeens hot in the Porcupine, Rockall andH atton basins,a sw ell asacross the Hatton continentalm argin. Integration ofthe wide-angleseismic datawithnormal-incidence reflection profilesandwithgravity andmagnetic datareveals a clearpictureofthe regionalcrustalanduppermantlestructure, andofthe large-scalesedimentary geometry ofthe LatePalaeozoic-Cenozoic basins inthe area.The region contains asetoflarge sedimentary basins restingupon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…In general, seismic studies have identified two crustal layers with low seismic velocity values representative of their continental affinity. However, the rifting processes that led to the formation of continental fragments and microcontinents most likely affect their layers and entire thicknesses (Morewood et al, 2005), as well as adding mafic intrusions to the crust. From 36 geophysical studies of continental fragments we determine an average crustal thickness of ∼ 24.8 ± 5.7 km (Table 5).…”
Section: Continental Fragments and Microcontinents: Crustal Structurementioning
confidence: 99%
See 2 more Smart Citations
“…In general, seismic studies have identified two crustal layers with low seismic velocity values representative of their continental affinity. However, the rifting processes that led to the formation of continental fragments and microcontinents most likely affect their layers and entire thicknesses (Morewood et al, 2005), as well as adding mafic intrusions to the crust. From 36 geophysical studies of continental fragments we determine an average crustal thickness of ∼ 24.8 ± 5.7 km (Table 5).…”
Section: Continental Fragments and Microcontinents: Crustal Structurementioning
confidence: 99%
“…In this region, continental fragments are accreting and colliding with arcs and (2003), (6) Klingelhoefer et al (2007), (7) Funck (2003), (8) Gerlings et al (2011), (9) Fowler et al (1989), (10) Breivik et al (2012), (11) Lebedeva-Ivanova et al (2006), (12) Morewood et al (2005), (13) Vogt et al (1998), and (14) Collier et al (2009). other continental fragments. The North Palawan block is the best example of a passive margin fragment currently impinging on an island arc (the Philippine Mobile Belt).…”
Section: Continental Fragments and Microcontinents: Accreted Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Irish continental shelf and many of the basins therein have been the focus of seismic reflection, seismic refraction and potential field investigations for several decades (Holder & Bott 1971;Whitmarsh et al 1974;Bunch 1979;Jacob et al 1985;Makris et al 1988;Roberts et al 1988;Lowe & Jacob 1989;O'Reilly et al 1991O'Reilly et al , 1995O'Reilly et al , 2010Vogt et al 1998;Landes et al 2000Landes et al , 2003Morewood et al 2005;Hauser et al 2008). Coupled with sparse well control, the resulting studies have allowed for the piecing together of the detailed tectonostratigraphic basin evolution of the margin (Shannon 1991;Naylor & Shannon 2009.…”
Section: The Irish Atlantic Marginmentioning
confidence: 99%
“…Seismic refraction data indicate that the crystalline crust beneath the southern part of the Rockall Basin is typically 5-7 km thick Morewood et al 2005). This is underlain by a 3-10 km-thick zone with P-wave velocities of 7.5-7.8 km s 21 , which was interpreted as a partially serpentinized upper mantle by O'Reilly et al (1996).…”
Section: Southern Rockall Basinmentioning
confidence: 99%